2022
DOI: 10.3390/jcm11092462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants on Pain Perception in Patients with Fibromyalgia—A Systematic Review

Abstract: In recent years, antioxidant supplements have become popular to counteract the effects of oxidative stress in fibromyalgia and one of its most distressing symptoms, pain. The aim of this systematic review was to summarize the effects of antioxidant supplementation on pain levels perceived by patients diagnosed with fibromyalgia. The words used respected the medical search terms related to our objective including antioxidants, fibromyalgia, pain, and supplementation. Seventeen relevant articles were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Chronic pain patients have benefitted from the development of a diet based on carbohydrates with low glycaemic index together with fruits and vegetables, yogurt, red wine, legumes and fish with occasional meat, eggs and cheese [55], while other workers have found evidence to support the use of olive oil, ancient grains, Mediterranean diet, glutamate and aspartame-free diet and a gluten-free diet in reducing symptoms of fibromyalgia [56]. A further systematic review of antioxidants in fibromyalgia suggested that over half of the studies assessed offered good evidence for efficacy of supplementation with vitamins and coenzyme Q10, and less consistent evidence for benefit from extra virgin olive oil and turmeric [57]. Vegan and FODMAP diets have produced some benefit in fibromyalgia [58] but significant differences in opinion persist at present [11,12,59].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain patients have benefitted from the development of a diet based on carbohydrates with low glycaemic index together with fruits and vegetables, yogurt, red wine, legumes and fish with occasional meat, eggs and cheese [55], while other workers have found evidence to support the use of olive oil, ancient grains, Mediterranean diet, glutamate and aspartame-free diet and a gluten-free diet in reducing symptoms of fibromyalgia [56]. A further systematic review of antioxidants in fibromyalgia suggested that over half of the studies assessed offered good evidence for efficacy of supplementation with vitamins and coenzyme Q10, and less consistent evidence for benefit from extra virgin olive oil and turmeric [57]. Vegan and FODMAP diets have produced some benefit in fibromyalgia [58] but significant differences in opinion persist at present [11,12,59].…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that future research and targeted therapy will be aimed at microvascular dysfunction and its role in the etiology and maintenance of symptoms in these and potential other chronic pain syndromes. These studies would add to the above-mentioned studies demonstrating the effectiveness of antioxidants or free radical scavengers as analgesics for CRPS ( 18 , 19 ) and fibromyalgia ( 40 ), and why combinations of topical agents aimed at improving both arterial and capillary blood flow ( 59 ), or salts and co-crystals comprised of vasodilators and antioxidants are effective analgesics in animal models of CRPS and neuropathic pain ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…FM patients also have higher levels of oxygen free radicals in blood mononuclear cells ( 38 ), and neutrophils from FM patients produce greater levels of the oxygen free radical hydrogen peroxide ( 39 ). This may explain why antioxidants have been useful as analgesics for fibromyalgia in some studies ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one can also assume that antioxidants can be used as a therapeutic method for soreness discomfort. Currently, numerous types of antioxidants have been tried in treating post-exercise soreness as well as FM discomfort 35 46 47. Among these, vitamins C, E and co-enzyme Q10 might be the most investigated agents.…”
Section: Discussionmentioning
confidence: 99%